Application of electrocoagulation in the removal of heavy metals in galvanic effluents - León Vilela, Ernesto (2021)
The search for new technologies aimed at treating industrial effluents has made electrocoagulation the most widely accepted emerging technology for treating galvanic effluents, which by their very nature contain high concentrations of heavy metals. The objective of this research is the effective elimination of the final heavy metal load through electrocoagulation in wastewater of galvanic origin, using aluminum (anode) and iron (cathode) electrodes, in a continuous reactor. The effects of parameters such as pH, current density and voltage, on the removal efficiencies of heavy metals were studied. The experimental results showed that the optimum pH where the highest removal percentages were reached was 6 (Chrome 96.8%, copper 98.1%, nickel 96.6% and zinc 98.1%). Removal efficiency was found to increase with an increase in voltage and current density, reaching 7.5 volts and 19 A / m2 the highest removal values respectively. It can be concluded, with the experimental results obtained, that electrocoagulation is very effective in removing heavy metals from galvanic effluents.